The Correlation between Sex, Age, Educational Background, and Hours of Service on Vigilance Level of ATC Officers in Air Nav Surabaya, Indonesia - Lalu Muhammad Saleh; Tjipto Suwandi; Hamidah Hamidah (International Journal of Evaluation and Research in Education (IJERE), 2016)
The vigilance of an Air Traffic Control (ATC) officer determines aviation safety. The number of aviation accidents tends to be increasing in recent years. Aviation accidents may be caused by human errors (i.e. errors made by pilot or ATC officer) or unsafe work condition. Sex, age, educational background, and hours of service might affect vigilance level of an ATC officer. This study was conducted to analyze the effect of sex, age, educational background and hours of service on ATC officers in Air Nav Surabaya vigilance level. This study applied cross-sectional study design with the number of samples was 41 staffs at Air Nav Surabaya. The obtained data were analyzed by using chi-square test. The results of data analysis indicated that sex, age, and educational background variables did not significantly affect vigilance level of ATC officers in Air Nav Surabaya as indicated by chi-square values of sex variable (p= 0.790), age variable (p= 0.241), and educational background variable (p= 0.335). Meanwhile, hours of service variable significantly affected ATC officer vigilance level as indicated by chi-square value (p) as much as 0.035. Based on these findings, it can be concluded that sex, age, and educational background variables did not correlate with ATC officers’ vigilance level while hours of service variable significantly correlated with ATC officers’ vigilance level.